(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Rough set theory, a powerful mathematical framework, excels in addressing uncertainty and imprecision. In this study, we explore the analysis and provide examples of ideals and prime ideals within imprecise scenarios, utilizing rough set theory to quantify and navigate the inherent imprecision and roughness within these algebraic structures. This research contributes to our comprehension of how rough set theory effectively manages imprecision in algebraic contexts.